2019
DOI: 10.12913/22998624/112405
|View full text |Cite
|
Sign up to set email alerts
|

Wear Characteristics of Hardfacing Coatings Obtained by Tungsten Inert Gas Method

Abstract: This paper evaluates the wear characteristics of hardfacing coatings. Regenerative hardfacing coatings were applied with the TIG (Tungsten Inert Gas) method. The solid welding wires were used to obtain the coatings marked as: EL-500 HB, EL-650 HB, and EL-3348. The tribological analysis of samples was conducted at room temperature. The wear rate was evaluated with a THT 1000 Anton Parr ball-on-disc tribotester, in accordance with the ASTM G-133 standard. The counterbody (static partner) consisted of balls with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The authors of the cited studies concluded that the microstructure of hardened steel had the main impact on the wear of the tested PCBN tools. These conclusions coincide with those of the current work [25][26][27].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The authors of the cited studies concluded that the microstructure of hardened steel had the main impact on the wear of the tested PCBN tools. These conclusions coincide with those of the current work [25][26][27].…”
supporting
confidence: 93%
“…During the operation of tools, along with the general principles of wear, special ones appear, often leading to their damage. Admittedly, the guides provide the permissible wear values at which the tool should be replaced, but they may differ significantly from those at which the cutting potential is fully used [25,26]. The dominant factor influencing the optimal conditions of tool operation is mainly damage caused by the wear of its cutting surfaces.…”
mentioning
confidence: 99%
“…It was revealed that an increase in carbon content increases the hardness, but also increases the brittleness of the hardfacing alloys. Dziedzic et al [25] tested regenerative hardfacing coatings applied with the tungsten inert gas. The multi-criteria analysis of the results of a ball-on-disk tribometer showed that the wear rate was the smallest for the samples with the highest hardness.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the presence of carbon in the friction surface reduces the adhesive interaction of contacting solids. On the other hand, it may reduce the lubrication efficiency [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%